2007
DOI: 10.1080/13607860600963695
|View full text |Cite
|
Sign up to set email alerts
|

Emotional impact of dementia diagnosis: Exploring persons with dementia and caregivers’ perspectives

Abstract: This paper examined the emotional impact of diagnosis disclosure on recently diagnosed people with dementia. Thirty patient/caregiver dyads attending a Geriatric Day Hospital Program in Ottawa, Canada participated in this qualitative exploratory study. Data sources included: (a) audio-tapes of diagnosis disclosure meeting, (b) in-depth interviews with patients and caregivers within one week of disclosure, and (c) focus group interviews with caregivers within one month. Patients exhibited a range of emotional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
159
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 32 publications
11
159
1
Order By: Relevance
“…After the initial shock of the diagnosis (Aminzadeh, Byszewski, Molnar, & Eisner, 2007), which some reported, they seem to have adapted rather well to the situation. In the early phases of the study, most of the informants find that their strategies for handling the life situation are sufficient for living a good life.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial shock of the diagnosis (Aminzadeh, Byszewski, Molnar, & Eisner, 2007), which some reported, they seem to have adapted rather well to the situation. In the early phases of the study, most of the informants find that their strategies for handling the life situation are sufficient for living a good life.…”
Section: Discussionmentioning
confidence: 99%
“…A range of reactions is reported, from positive responses through to depression, grief, and active denial. [21][22][23] Studies of individuals undergoing assessment (and of their carers) have revealed equivocal views about the adequacy of information supplied, 24 and concerns about clinicians' ability to identify information needs and respond effectively; 25 observations that have similarly arisen in the Netherlands. 26,27 A literature review undertaken as part of the current study, which focused on the process of disclosure of dementia diagnosis, revealed wide variability in reported practice, with theoretical 'guidelines' that did not reflect practice.…”
Section: Resultsmentioning
confidence: 99%
“…Given the combination of powerful emotional responses to dementia (Aminzadeh et al, 2007;Connell et al, 2004) and the desire of most people to know about their illness (Ouimet et al, 2004;Elson, 2006;Jha, Tabet and Orrell;2001), it is perhaps unsurprising that psychotherapeutic approaches with people affected by dementia have been consistently reported over the last twenty years. Reports of group therapy interventions, including support groups and a range of psychotherapy interventions are at least as common as descriptions of individual interventions (Cheston, 1998) or couple psychotherapy (Auclair, 2009).…”
Section: Introductionmentioning
confidence: 99%